Aspek Pemasaran pada Bisnis Her Haven Guest House di Jakarta Pusat - Yulius, Kevin Gustian; Wilson, Richard (PERWIRA - Jurnal Pendidikan Kewirausahaan Indonesia, 2024)
This study aims to access the potential market for the establishment of Her Haven Guest House, a specialized accommodation designed for female travellers which located in Central of Jakarta. A market survey being used for the research methodology, where the author distributed the questionnaires to the targeted respondents. The study focused on the market and marketing analysis, where the author used SWOT analysis and Porter’s Five Forces. SWOT analysis being used to identify the strength, weakness, opportunities, and threat, while the Porter’s Five Forces being used to identify the level of competitive in accommodation industry. This analysis is conducted to understand the opportunities and the competitive that need to be encounter by Her Haven Guest House. The outcomes of this study are expected to provide insight for the market potential that Her Haven Guest House could have. Additionally, the author hoping that this study might be used as reference for the potential investor seeking to invest in specialized accommodation for female.